2019
DOI: 10.3390/ijms20040924
|View full text |Cite
|
Sign up to set email alerts
|

IRES Trans-Acting Factors, Key Actors of the Stress Response

Abstract: The cellular stress response corresponds to the molecular changes that a cell undergoes in response to various environmental stimuli. It induces drastic changes in the regulation of gene expression at transcriptional and posttranscriptional levels. Actually, translation is strongly affected with a blockade of the classical cap-dependent mechanism, whereas alternative mechanisms are activated to support the translation of specific mRNAs. A major mechanism involved in stress-activated translation is the internal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
147
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(147 citation statements)
references
References 211 publications
(214 reference statements)
0
147
0
Order By: Relevance
“…IRESs, elements located in the leader region of a restricted class of mRNA, allow the initiation of mRNA translation independently on the Cap-structure [25,36,37]. The alternative mechanism of translation mediated by IRESs is important when the attenuation of global protein synthesis occurs in cells undergoing stress conditions, such as ER stress, hypoxia, UV irradiation, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IRESs, elements located in the leader region of a restricted class of mRNA, allow the initiation of mRNA translation independently on the Cap-structure [25,36,37]. The alternative mechanism of translation mediated by IRESs is important when the attenuation of global protein synthesis occurs in cells undergoing stress conditions, such as ER stress, hypoxia, UV irradiation, etc.…”
Section: Discussionmentioning
confidence: 99%
“…IRES-mediated Cap-independent translation is often supported by IRES trans-activating factors (ITAFs) [36]. In recent studies, it has been shown an increase of the SREBP-1a expression dependent on binding of hnRNP A1 on SREBP-1a 5 UTR [9,40].…”
Section: Discussionmentioning
confidence: 99%
“…Several cellular mRNAs were found to contain IRESs in their 5 UTR in addition to the 5 cap, implying that their translation can initiate through both cap-dependent and cap-independent mechanisms. In addition, different IRES elements interact with other trans-acting factors during initiation [81,82].…”
Section: Iressmentioning
confidence: 99%
“…Indeed, in the absence of cap-binding machinery or when cap-dependent initiation has been inhibited following cellular stress, alternative mechanisms can be initiated to ensure that proteins required for cell survival remain expressed. Several modes of translation have been proposed to explain cap-independent translation of mammalian mRNA with internal ribosomal entry site (IRES) being the most studied so far [17,18]. IRES-dependent initiation and current research in gliomas will be discussed hereafter.…”
Section: Overview On Translation Initiationmentioning
confidence: 99%